2020
DOI: 10.3346/jkms.2020.35.e195
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of a High SARS-CoV-2 Viral Load in the Saliva

Abstract: Background: Patients with coronavirus disease 2019 (COVID-19) can unknowingly spread the virus to several people during the early subclinical period. Methods: We evaluated the viral dynamics in various body fluid specimens, such as nasopharyngeal swab, oropharyngeal swab, saliva, sputum, and urine specimens, of two patients with COVID-19 from hospital day 1 to 9. Additional samples of the saliva were taken at 1 hour, 2 hours, and 4 hours after using a chlorhexidine mouthwash. The severe acute respiratory syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
352
0
17

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(404 citation statements)
references
References 14 publications
16
352
0
17
Order By: Relevance
“…Other reports have suggested that SARS-CoV-2 is shed into saliva at a remarkably wide range from 10,000-10,000,000,000 copies/mL. 12,26 While the LOD of SARS-CoV-2 approved diagnostic methods can vary considerably (500-80,000 viral copies/mL 39 ) and are not always reported, the best LOD values for SARS-CoV-2 using RNA extraction protocols appear to be approximately 1000 copies/mL. 28 Similarly, a LOD of 5610 copies/mL was found for SARS-CoV-2 detection in saliva using RNA purification.…”
Section: Limit Of Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports have suggested that SARS-CoV-2 is shed into saliva at a remarkably wide range from 10,000-10,000,000,000 copies/mL. 12,26 While the LOD of SARS-CoV-2 approved diagnostic methods can vary considerably (500-80,000 viral copies/mL 39 ) and are not always reported, the best LOD values for SARS-CoV-2 using RNA extraction protocols appear to be approximately 1000 copies/mL. 28 Similarly, a LOD of 5610 copies/mL was found for SARS-CoV-2 detection in saliva using RNA purification.…”
Section: Limit Of Detectionmentioning
confidence: 99%
“…24 Compounding these anatomic limitations, the procedure for NP sample collection is invasive, further reducing patient compliance for repeated and serial sampling. Saliva may serve as an important mediator in transmitting SARS-CoV-2 between individuals via droplets and aerosols, [25][26][27] and thus viral loads in saliva may serve as a highly relevant correlate of transmission potential. However, saliva is comprised of constituents that may hinder virus detection by RT-qPCR, such as degradative enzymes.…”
Section: Development Of a Direct Saliva-to-rt-qpcr Process For Detectmentioning
confidence: 99%
“…Coronaviruses are a group of enveloped RNA viruses that present a typical structure with the "spike protein" in its membrane envelope. 6,7 The interaction between this protein and angiotensin-converting enzyme 2 (ACE2) receptors is responsible for the entry of the virus into cells. 8 The distribution of ACE2 receptors in different parts of the body may indicate possible routes of infection.…”
Section: Pathogenesis Of Coronavirus Disease 2019mentioning
confidence: 99%
“…22 Although COVID-19 is an enveloped virus, 0.12% CHX gluconate was suggested to have little or no effect against coronaviruses when compared with other mouthwashes. 4,23,24 However, Yoon et al 6 found SARS-CoV-2 suppression for two hours after using 15 ml 0.12% CHX once, suggesting that its use would be beneficial for the control of COVID-19 transmission.…”
Section: Chlorhexidine (Chx)mentioning
confidence: 99%
“…The difference in sensitivity probably reflects differences in the clinical background and timing of sampling in each study. In fact, several studies reported reduced viral load in saliva with time Iwasaki et al 2020;Nagura-Ikeda et al 2020;Williams et al 2020;Yoon et al 2020;Zhang et al 2020;Zhu et al 2020). However, the specificity ranging from 97% to 100% suggests reliable detection limits of current assays for detecting the absence of SARS-CoV-2 viral loads in saliva samples.…”
Section: Population-level Employable Rapid Testing Strategy: Advantagmentioning
confidence: 99%